Jewish and Islamic Philosophy : Crosspollinations in the Classic Age - Goodman, Lenn Evan, 1944- (Book collections on Project MUSE., 1999)
"The object of Goodman's discussion is not to find the "sources" of religious ideas (as if to credit the philosophical originality of one tradition or cast aspersions on the philosophical dependency of another), but rather to explicate, connect, and demonstrate the commonalities of these two competing yet inextricably linked religious and philosophical traditions."--BOOK JACKET. "It is sure to become a key text for all students in religious studies, Jewish and Islamic studies, and philosophy."--Jacket.